A Series on Diseases in the Florida Vegetable Garden: PEPPER - Ken Pernezny; Tim Momol (EDIS, 2004)
The majority of plant health problems categorized as plant diseases are caused by microorganisms. As the name implies, these are extremely tiny disease agents that ordinarily require a microscope to be seen. The very minute size of these disease-causing pathogens accounts for the mystery that often surrounds their presence and impact in the garden. The pathogenic microorganisms that attack garden vegetables, including pepper, can be classified into three major groups: fungi, bacteria, and viruses. This document is Fact Sheet PP-201, one of a series of the Plant Pathology Department, Florida Cooperative Extension Services, Institute of Food and Agricultural Sciences, University of Florida. Published July 2004.